Cloud computing and security issue (International Journal of Engineering and Computer Science, 2016)
Cloud computing has make the conceptual and structural basis for tomorrow’s computing. The World computing structure is rapidly moving towards cloud based architecture. While it is important to take advantages of could based computing by means of moving it in diversified sectors, the security aspects in a cloud based computing environment is most important. Cloud based services and service providers are being evolved which has resulted in a new business trend based on cloud technology. With the introduction of large number of cloud based services and geographically differ cloud service providers, sensitive information of different entities are normally stored in remote servers and locations with the possibilities of being exposed to unauthorized access in situations where the cloud servers storing those information are compromised. If security is not strong and consistent, the flexibility and advantages that cloud computing has to offer will have little credibility. In this paper security in cloud computing is elaborated in a way that covers security issues, concerns and challenges for Data Security in Cloud. This paper presents a review on the cloud computing concepts as well as security issues inherent within the context of cloud computing and cloud structure.